Improving Learning Outcomes on Symbiosis Material Using the Make A Match Model for Elementary School Students - Roja'i Roja'i; Nanang Alamsyah (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2023)
This research aims to determine the implementation of the Make a Match learning model in improving science learning outcomes in symbiosis material for class V students at SDN 1 Banding Agung. This type of research is Classroom Action Research (CAR) with research subjects being class V students at SDN 1 Banding Agung consisting of 13 male students and 17 female students. The data collection technique used was a post-test in the form of multiple choice questions and essays. The action research procedure consists of two cycles. Each cycle goes through four research stages including planning, action, observation and reflection. The data analysis technique used is quantitative descriptive. Based on the research results, the percentage of completeness of learning outcomes in the pre-cycle showed a percentage of only 30%, while in the first cycle of action the minimum percentage of completeness of students was 73.3% or an increase of 43.3% from the pre-cycle. In cycle II the actions continued to increase with a minimum percentage of completeness of 100% or an increase of 26.7% from cycle I to cycle II, and an increase of 70% from pre-cycle to cycle II. The learning improvement results obtained in cycle II were in accordance with the researcher's objectives, namely to improve science learning outcomes in symbiosis material for class V students at SDN 1 Banding Agung, Talang Padang sub-district, Tanggamus Regency.